Evaluate the implementation of the investment plan projects A study on the field of the plan projects for the period 2013-2016 - لفته عبد السلام; احمد احمد وليد (Journal of Economics and Administrative Sciences, 2018)
The main problem of this research is the delay of implementation of the investment plan projects for the period (2013-2016) and the weakness of the staff ability in the ministries and they don’t have the sufficient experience to carry out the implementation process. Therefore, the research aims to evaluate the implementation of programs and projects of the investment plan in a manner consistent with the objectives set for them without any wasteful of efforts, time and money. And then identify the problems and obstacles to determine the deviations of the implementation of the specific for each sector according to the criteria of evaluation and the form of cost, quality, time and implementation. And on the premise that the use of criteria for evaluation of the implementation of investment projects through the analysis of problems and obstacles encountered in the field will lead to the results are close to reality and provide a high degree of confidence in making corrective decisions for the stage of implementation of projects and avoid falling into the same mistakes when taking Future investment decisions. The research is based on the analytical field study of indicators of implementation of investment plan projects in the Iraqi Ministry of Planning for the period (2013-2016) Through it reached several conclusions, the most important of them is the weakness of the efficiency of contractors and contractors companies by using determinants of projects to use criteria for evaluation, while not following the scientific basis for setting these determinants,The recommendations of the research are the necessary possibilities and recommendations to solve the problems that were the cause of low rates of financial and material implementation and the emergence and increasing of problems.